Rise and growth of economic nationalism in India - Chandra, Bipan (New Delhi, 1966)
The process of freedom from British rule in India began early in the last century. The movement passed through many vicissitudes and had many strands but its essential character was that of a peaceful revolution. When the first tide of resis tance to the advance of alien domination had nearly exhaust ed itself and the opposition offered by the Indian States, the first victims of aggressive imperialism, had dissolved, the emerging educated urban middle class adopted the method of constitutional agitation for seeking a voice in the adminis tration of the country. Their main instrument of action was the public press and the political or social associations whose forum was utilised for pressing the needs of the people and removing their grievances. This early expression of public opinion, confined largely to the Presidency towns, had only one object, that of submitting representations to the authori ties. It was pre-eminently an appeal to the conscience of England, to the sense of justice and spirit of liberalism which then prevailed in that country. Many Indian administrators were inspired by utilitarian ideas and had firm faith in paternalism as the only principle of state action in India. Yet their policies were fashioned not by considerations of the welfare of the Indian people but by the motives of profit of the East India Company and development of industry and progress and prosperity of the British people.
Keywords: Economics